Bryoerythrophyllum campylocarpum (Müll.Hal.) H.A.Crum, a tropical and subtropical moss new to Ireland and Britain. (2nd October 2021) - Ottley, Tom; Blockeel, Tom L.; Kučera, Jan
ABSTRACT: Introduction: An unfamiliar member of the Pottiaceae discovered near Goginan in Cardiganshire, Wales, UK, was identified as Bryoerythrophyllum campylocarpum sensu lato. An earlier collection from a wood in East Cork, Ireland, was subsequently confirmed as belonging to the same species. This moss is primarily a tropical and subtropical species and is very rare in Europe. Methods: Both the Irish and Welsh plants were initially identified by morphological comparison with herbarium specimens of Bryoerythrophyllum campylocarpum from other areas of its distribution. Identification was confirmed by assessment of molecular affinities using two chloroplast markers, rps4 and trn M– trn V. Key results and conclusions: Molecular and morphological affinities are presented and discussed. Comparisons are made with similar species and notes on identification are presented. Bryoerythrophyllum campylocarpum, as currently circumscribed, is confirmed as a member of the Irish and British bryophyte floras; however, both the molecular and morphological variation of specimens attributed to this species suggest that it is a collective taxon comprising at least three lineages which will probably need to be described as species in the future. The possible origins of the Irish and Welsh plants are considered.